Excision of a sclerosing polycystic adenosis of the deep parotid gland. Issue 5 (29th December 2021) - Moyer, Erik; Swid, Mohammed Amer; Tuliszewski, Robert; Barrese, James; Mock, Jeremy; Frank, Renee
Abstract: A 15‐year‐old male presented to the hospital with a 2‐month history of a right parotid mass. Magnetic resonance imaging revealed an encapsulated 3.7 cm mass. Fine‐needle aspiration suggested a monomorphic adenoma (prior to utilization of the Milan Classification system). Total parotidectomy was performed with dissection and preservation of the facial nerve. Surgical pathology identified the lesion as sclerosing polycystic adenosis (SPA) after examining the histopathological and immunohistochemistry findings. SPA is a rare lesion which leads to inflammatory changes in the salivary gland. The most common site impacted is the parotid gland but also can affect other major or minor salivary glands. The fibrocystic changes are morphologically like the histological developments of sclerosing adenosis of breast tissue. Those changes consist of fibrosis, apocrine metaplasia, and different degrees of proliferation of ducts, acini, and myoepithelial cells. The pathogenesis of SPA is unknown but recent studies suggest that it could be a neoplasm. Treatment with surgical excision is effective and its' recurrence is rare. This case report details the cytomorphology, histology, and immunohistochemical profile of SPA.